Preparation method and application of modified heat-conducting insulating filler based on polyphenol compounds
By modifying the thermally conductive insulating filler surface by surface modification of polyphenol compounds and silane coupling agents, an enriched layer is formed, which solves the problem of increased viscosity and low compatibility of ceramic thermally conductive filler in electronic packaging materials, and achieves efficient thermal conductivity Combined with insulation performance, simplifies the process flow and improves output.
Patent Information
- Application Number
- CN202411256952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Existing ceramic thermal fillers are difficult to achieve a combination of efficient thermal conductivity and insulation properties in industrial applications due to increased viscosity and low compatibility, especially in electronic packaging materials.
The thermally conductive insulating filler is surface modified by polyphenol compounds (such as dopamine, catechol, tannic acid, catechol) and silane coupling agent HMDS, and enrichment is formed through amide bond condensation and silicon-oxygen bond reaction. The layer improves the dispersion and thermal conductivity of the filler and is evenly dispersed in the silicone rubber.
It significantly improves the compatibility and dispersion of thermally conductive fillers, enhances the thermal conductivity and insulation properties of composite materials, simplifies the process flow, and improves output.
Smart Images

Figure BDA0005034378140000041 
Figure BDA0005034378140000061 
Figure BDA0005034378140000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermally conductive insulating fillers, and more specifically relates to a preparation method and application of a thermally conductive insulating filler modified by polyphenol compounds. Background Art
[0002] In recent years, with the vigorous development of semiconductor industry technology, electronic devices are often integrated, dense, lightweight and multifunctional, and the thermal properties of materials are crucial to the regular use and life of components. Therefore, finding thermal interface materials with high thermal conductivity, excellent thermal stability and insulation properties is a hot topic in today's electronics industry. Among them, polymers are of great interest in electronic packaging due to their excellent expansion properties, light weight and low cost. However, the thermal conductivity of pure polymers is low (less than 0.25W / m·K), so some fillers (metal fillers, ceramic materials and carbon-based materials) are often used in blends to improve the thermal conductivity of composite materials.
[0003] Ceramic thermal conductive fillers have good thermal conductivity and excellent electrical insulation, such as boron nitride, aluminum nitride, silicon nitride, etc. Boron nitride materials have become one of the current research hotspots due to their high thermal conductivity, excellent electrical insulation, low density and other properties. However, as pure boron nitride is filled into a large matrix, the viscosity of the composite material increases sharply with the increase in content, and the compatibility between boron nitride and the matrix is low, making it difficult to use it in large quantities in industrial applications. Therefore, a direct method is to enhance the interaction between the filler and the matrix by modifying the surface of boron nitride, thereby improving the thermal conductivity of the composite material. Polyphenol compounds such as dopamine, catechol, tannic acid, catechol and gallic acid contain multiple phenolic groups, have the characteristics of oxidative polymerization, coordination complexation, adhesion, biocompatibility, free radical scavenging, light absorption, etc., and have been widely used in material surface functionalization modification. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a preparation method and application of a thermally conductive insulating filler modified by polyphenol compounds. The present invention uses polyphenol compounds and silane coupling agent HMDS to modify the surface of the thermally conductive insulating filler. The polyphenol compounds include dopamine, catechol, tannic acid, catechol and gallic acid, etc., and their surfaces contain a large number of active groups, such as hydroxyl groups, amino groups, etc.; the surface of the material modified by the polyphenol compounds often shows a large number of active groups such as hydroxyl groups to reduce the surface thermal resistance of BN and silicone rubber materials; the polyphenol compounds are then used to react with the hydroxyl groups on the surface of chitosan under alkaline conditions to form an enrichment layer; this enrichment layer interacts with the amino groups and hydroxyl groups on the surface of the thermally conductive filler modified by the polyphenol compounds to form new functional groups such as hydroxyl groups and ketone groups. These functional groups can provide physical cross-linking, metal complexation, hydrogen bonding and other interactions to improve the dispersibility of the thermally conductive filler in silicone rubber; the addition of chitosan makes the thermally conductive filler evenly dispersed to form an effective thermal conductive path. Finally, the surface is modified with a silane coupling agent. The silane coupling agent HMDS can form an active layer on the surface of the solid powder. Its mechanism of action is that the silicon-oxygen bond in the silane molecule reacts with the hydroxyl group to form a hydrogen bond and condense into a -SiO-M covalent bond (M represents a group on the surface of the thermal conductive filler), thereby achieving surface modification and reducing the surface roughness of the composite material.
[0005] In order to achieve the above object, the present invention is implemented by the following technical scheme: a preparation method based on polyphenol compound modified thermal conductive insulating filler, comprising the following steps:
[0006] Step 1: Disperse the thermally conductive insulating filler in water, add an alkaline solvent and a polyphenol compound, and stir until the mixture is uniformly mixed; the resulting solution is washed, centrifuged, dried, and ground to obtain a solid powder;
[0007] Step 2: dropping a hydrogen peroxide aqueous solution into a chitosan-acetic acid aqueous solution, and after reaction, obtaining low molecular weight chitosan;
[0008] Step 3: adding low molecular weight chitosan to an alkaline solvent for ultrasonic dispersion, then adding solid powder for stirring, washing and drying to obtain a modified solid powder;
[0009] Step 4: Mix the modified solid powder with hexamethyldisilazane and stir evenly. After the obtained solution reacts in a reactor, it is dried and ground to obtain a modified thermally conductive insulating filler.
[0010] Further preferably, in step 1, the ratio of the added amounts of the thermally conductive insulating filler, water, alkaline solvent and polyphenol compound is 0.8-2g:150-300mL:0.6-1g:0.4-1g.
[0011] Further preferably, in step one, the thermally conductive insulating filler is a mixture of one or more of boron nitride, aluminum nitride, and silicon nitride; the thermally conductive insulating filler is dispersed in water, ultrasonicated for 3-4 hours and stirred for 2-3 hours, and then an alkaline solvent and a polyphenol compound are added.
[0012] Further preferably, in step 1, the alkaline solvent is one of Tris-HCl buffer, sodium carbonate, sodium bicarbonate and borate buffer.
[0013] Creating weakly alkaline conditions facilitates the polymerization of polyphenol compounds.
[0014] Further preferably, in step 1, the polyphenol compound is one of dopamine, catechol, tannic acid, catechol and gallic acid.
[0015] For example, dopamine (DA) can be polymerized under alkaline conditions to form polydopamine (PDA), which can efficiently adhere to the surface of objects. DA is a good biomodification of polymers, covering the surface of fillers with amino and hydroxyl groups to reduce the surface thermal resistance of BN and silicone rubber materials.
[0016] Further preferably, in step 1, the stirring is: stirring in a water bath at 60-70° C., a rotation speed of 400-600 r / min, and continuous stirring time of 12-24 h.
[0017] Further preferably, in step 1, the drying conditions are: 50-60° C., 12-18 h.
[0018] Further preferably, in step 2, the stirring is: stirring in a water bath at 60-70° C., a rotation speed of 400-600 r / min, and a continuous stirring time of 8-12 h.
[0019] Further preferably, in step 2, the mass concentration of the aqueous hydrogen peroxide solution is 5-6%; in the chitosan-acetic acid aqueous solution, the mass concentration of chitosan is 0.1 kg / L, and the mass concentration of acetic acid is 2-3%; the molecular weight of the chitosan is 100 KDa; and the molecular weight of the obtained low molecular weight chitosan is 40-60 KDa.
[0020] Further preferably, in step three, the mass ratio of the low molecular weight chitosan, the alkaline solvent and the solid powder is 1:100:1.5-1.7; the alkaline solvent is one of Tris-HCl buffer, sodium carbonate, sodium bicarbonate and borate buffer; and the stirring is stirring at room temperature for 24-30 hours.
[0021] Further preferably, in step 4, the mass ratio of the modified solid powder to hexamethyldisilazane is 5:4.
[0022] Further preferably, in step 4, the reaction conditions of the reactor are: temperature of 85-90° C., and duration of 2-3 h.
[0023] Further preferably, in step 4, the drying conditions are: temperature of 150-160° C., duration of 6-12 hours.
[0024] The second technical solution of the present invention: an application of the modified thermally conductive insulating filler obtained by the above preparation method in silicone potting glue.
[0025] Further preferably, vinyl silicone oil and hydrogen-containing silicone oil are used as base polymers, and modified thermally conductive insulating fillers are used as additives. The vinyl silicone oil and fillers are mixed to obtain a silicone-based adhesive. The silicone-based adhesive is mixed with hydrogen-containing silicone oil and a platinum catalyst to undergo catalytic cross-linking to obtain a thermally conductive insulating silicone potting adhesive. The amount of thermally conductive insulating filler added is 10%-30% of the mass of the silicone-based adhesive.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] (1) The process is simple and the yield is high; (2) Polyphenol compound modification has the characteristics of oxidative polymerization, coordination complexation, adhesion, etc. The thermal conductive insulating filler is modified with polyphenol compounds to achieve excellent coating properties and improve the compatibility and dispersibility of the thermal conductive insulating filler; (3) The addition of chitosan makes the thermal conductive filler evenly dispersed, forming an effective thermal conductive path, and it has excellent thermal conductive and insulating properties when used in silicone rubber. DETAILED DESCRIPTION
[0028] The technical content and effects of the present invention are further described in detail below in conjunction with the embodiments, but the present invention is not limited thereto.
[0029] Example 1
[0030] (1) Disperse 1 g of boron nitride in 150 g of deionized water, ultrasonicate for 3 h, and stir evenly.
[0031] (2) Add 0.6 g Tris-HCl buffer (pH = 8.0) and 0.6 g dopamine (DA) to the mixed solution obtained in step (1), stir in a water bath at 60° C. for 12 h at a speed of 500 r / min, and finally dry at 60° C. for 12 h to obtain BN@PDA.
[0032] (3) Add 5 g of 5 wt% H2O2 aqueous solution to 10 g of chitosan-acetic acid aqueous solution (containing 1 g of chitosan, 2 wt% of acetic acid, and an average molecular weight of chitosan of 100 KDa), stir in a water bath at 60°C for 8 h at a speed of 500 r / min, and filter through two layers of filter paper after cooling; adjust the pH of the filtrate to 10 with strong base NaOH, let stand for 2 h, and filter again with two layers of filter paper; concentrate the filtrate under reduced pressure, dilute with methanol, let stand for 5 h, collect the white precipitate by filtration, wash with methanol, and finally dry in a vacuum at 40°C for 8 h to obtain low molecular weight chitosan.
[0033] (4) Take 0.6 g of Tris-HCl buffer (pH = 8.0) and add it to 100 g of deionized water, disperse 1 g of low molecular weight chitosan in it, and ultrasonicate for 1 h; then add 1.6 g of BN@PDA, stir at room temperature for 24 h, wash with deionized water and ethanol three times, and vacuum dry at 60 ° C for 12 h to obtain BN@PDA-Chitosan.
[0034] (5) Mix BN@PDA-Chitosan and silane coupling agent hexamethyldisilazane (HMDS) in a mass ratio of 5:4 and stir evenly.
[0035] (6) The obtained solution was reacted in a reactor at 85 °C for 3 h, and then dried and ground at 150 °C to obtain BN@PDA-Chitosan-HMDS.
[0036] Add 4g BN@PDA, 4g BN@PDA-Chitosan, and 4g BN@PDA-Chitosan-HMDS to 16g vinyl silicone oil, mix well, and obtain 20g of silicone-based glue. Mix 10g of silicone-based glue and 0.01g of platinum catalyst (chloroplatinic acid) to obtain component A, and mix 10g of silicone-based glue and 1g of hydrogen-containing silicone oil to obtain component B. Mix components A and B in a mass ratio of 1:1, put them in a vacuum drying oven at 30℃ for degassing for 30min, pour them into a mold and cure them at room temperature for 12h to obtain a thermally conductive and insulating silicone potting glue, test its thermal conductivity, and repeat 3 times.
[0037] Table 1
[0038]
[0039] As shown in Table 1, the filling amount of the thermally conductive filler is 20% of the mass of the silicone-based glue. It can be clearly seen that the addition of the thermally conductive filler significantly improves the thermal conductivity of the silicone potting glue. After modification with dopamine, its thermal conductivity is further improved; chitosan is added to the surface of dopamine for Michael addition reaction, which further increases the active groups on the surface of the thermally conductive filler, improves the dispersibility, and increases the thermal conductivity; HMDS is grafted on the surface for surface modification and cleaning, which is more conducive to the dispersion of the thermally conductive filler, improves the dispersion of the filler, forms more thermal conductive networks in the silicone potting glue, and increases the thermal conductivity.
[0040] With the addition of thermal conductive fillers, the volume resistance of silicone potting compound decreases. The reason for this phenomenon is that the BN modified by PDA forms more ion channels. Under the activation of external current, the weakly conductive ions in the silicone potting compound can form more conductive channels without passing through the BN surface, thereby reducing the resistance; but the overall volume resistance is very large, which can fully meet the necessary conditions for silicone potting compound to achieve good electronic insulation as a packaging material.
[0041] Example 2
[0042] (1) Disperse 1 g of boron nitride in 150 g of deionized water, ultrasonicate for 3 h, and stir evenly.
[0043] (2) Add 0.5 g of sodium bicarbonate and 0.5 g of tannic acid (TA) to the mixed solution obtained in step (1), stir in a water bath at 60° C. for 12 h at a speed of 500 r / min, and finally dry at 60° C. for 12 h to obtain BN@PTA.
[0044] (3) Add 5 g of 5 wt% H2O2 aqueous solution to 10 g of chitosan-acetic acid aqueous solution (containing 1 g of chitosan, 2 wt% of acetic acid, and an average molecular weight of chitosan of 100 KDa), stir in a water bath at 60°C for 8 h at a speed of 500 r / min, and filter through two layers of filter paper after cooling; adjust the pH of the filtrate to 10 with strong base NaOH, let stand for 2 h, and filter again with two layers of filter paper; concentrate the filtrate under reduced pressure, dilute with methanol, let stand for 5 h, collect the white precipitate by filtration, wash with methanol, and finally dry in a vacuum at 40°C for 8 h to obtain low molecular weight chitosan.
[0045] (4) Take 0.5 g of sodium bicarbonate and add it to 100 g of deionized water, disperse 1 g of low molecular weight chitosan in it, and ultrasonicate for 1 h; then add 1.6 g of BN@PTA, stir at room temperature for 24 h, wash with deionized water and ethanol for 3 times, and vacuum dry at 60 ° C for 12 h to obtain BN@PTA-Chitosan.
[0046] (5) Mix BN@PTA-Chitosan and silane coupling agent hexamethyldisilazane (HMDS) in a mass ratio of 5:4 and stir evenly.
[0047] (6) The obtained solution was reacted in a reactor at 85 °C for 3 h, and then dried and ground at 150 °C to obtain BN@PTA-Chitosan-HMDS.
[0048] Add 4g BN@PTA, 4g BN@PTA-Chitosan and 4g BN@PTA-Chitosan-HMDS to 16g vinyl silicone oil respectively, mix well to obtain 20g silicone-based adhesive; mix 10g silicone-based adhesive and 0.01g platinum catalyst (chloroplatinic acid) well to obtain component A; mix 10g silicone-based adhesive and 1g hydrogen-containing silicone oil well to obtain component B; mix components A and B in a mass ratio of 1:1, put them in a vacuum drying oven at 30℃ for degassing for 30min, pour them into a mold and cure them at room temperature for 12h to obtain a thermally conductive insulating silicone potting adhesive, test its thermal conductivity, and repeat 3 times.
[0049] Table 2
[0050]
[0051] As shown in Table 2, compared with Example 1, the thermal conductivity of the composite material obtained by modifying boron nitride with tannic acid is higher than that obtained by modifying boron nitride with dopamine; tannic acid is a polyphenol compound extracted from natural plants, rich in catechol and pyrogallol groups, can quickly self-polymerize to form PTA under alkaline conditions, has a fast reaction speed, complete coating, and has more active groups than dopamine. Therefore, the performance of the obtained silicone potting compound is better.
[0052] Example 3
[0053] (1) Disperse 1 g of boron nitride in 150 g of deionized water, ultrasonicate for 3 h, and stir evenly.
[0054] (2) To the mixed solution obtained in step (1), 0.6 g of Tris-HCl buffer (pH = 8.0) and 0.6 g of dopamine (DA) were added, stirred in a water bath at 60° C. for 12 h at a speed of 500 r / min, and finally dried at 60° C. for 12 h to obtain BN@PDA.
[0055] (3) Add 5 g of 5 wt% H2O2 aqueous solution to 10 g of chitosan-acetic acid aqueous solution (containing 1 g of chitosan, 2 wt% of acetic acid, and an average molecular weight of chitosan of 100 KDa), stir in a water bath at 60°C for 8 h at a speed of 500 r / min, and filter through two layers of filter paper after cooling; adjust the pH of the filtrate to 10 with strong base NaOH, let stand for 2 h, and filter again with two layers of filter paper; concentrate the filtrate under reduced pressure, dilute with methanol, let stand for 5 h, collect the white precipitate by filtration, wash with methanol, and finally dry in a vacuum at 40°C for 8 h to obtain low molecular weight chitosan.
[0056] (4) Take 0.6 g of Tris-HCl buffer (pH = 8.0) and add it to 100 g of deionized water, disperse 1 g of low molecular weight chitosan in it, and ultrasonicate for 1 h; then add 1.6 g of BN@PDA, stir at room temperature for 24 h, wash with deionized water and ethanol three times, and vacuum dry at 60 ° C for 12 h to obtain BN@PDA-Chitosan.
[0057] (5) Mix BN@PDA-Chitosan and silane coupling agent hexamethyldisilazane (HMDS) in a mass ratio of 5:4 and stir evenly.
[0058] (6) The obtained solution was reacted in a reactor at 85 °C for 3 h, and then dried and ground at 150 °C to obtain BN@PDA-Chitosan-HMDS.
[0059] Add 2g BN@PDA-Chitosan-HMDS, 4g BN@PDA-Chitosan, and 6g BN@PDA-Chitosan-HMDS to the vinyl silicone oil, mix well, and obtain 20g of silicone-based adhesive. Mix 10g of silicone-based adhesive and 0.01g of platinum catalyst (chloroplatinic acid) to obtain component A, and mix 10g of silicone-based adhesive and 1g of hydrogen-containing silicone oil to obtain component B. Mix components A and B in a mass ratio of 1:1, put them in a vacuum drying oven at 30℃ for degassing for 30 minutes, pour them into a mold and cure them at room temperature for 12 hours to obtain a thermally conductive and insulating silicone potting adhesive, test its thermal conductivity, and repeat 3 times.
[0060] Table 3
[0061]
[0062] As shown in Table 3, with the increase of the content of thermal conductive filler, more effective thermal conductive paths are formed, and the thermal conductivity of the silicone potting compound increases. However, a large amount of thermal conductive filler will cause the viscosity of the system to increase and the intermolecular force to increase. The basis of heat conduction is the mutual collision between molecules. Therefore, with the increase of the viscosity of the system, the thermal conductivity decreases.
[0063] Comparative Example 1 (the silane coupling agent used for modification is different from that in Example 1)
[0064] (1) Disperse 1 g of boron nitride in 150 g of deionized water, ultrasonicate for 3 h, and stir evenly.
[0065] (2) Add 0.6 g Tris-HCl buffer (pH = 8.0) and 0.6 g dopamine (DA) to the mixed solution obtained in step (1), stir in a water bath at 60° C. for 12 h at a speed of 500 r / min, and finally dry at 60° C. for 12 h to obtain BN@PDA.
[0066] (3) Add 5 g of 5 wt% H2O2 aqueous solution to 10 g of chitosan-acetic acid aqueous solution (containing 1 g of chitosan, 2 wt% of acetic acid, and an average molecular weight of chitosan of 100 KDa), stir in a water bath at 60°C for 8 h at a speed of 500 r / min, and filter through two layers of filter paper after cooling; adjust the pH of the filtrate to 10 with strong base NaOH, let stand for 2 h, and filter again with two layers of filter paper; concentrate the filtrate under reduced pressure, dilute with methanol, let stand for 5 h, collect the white precipitate by filtration, wash with methanol, and finally dry in a vacuum at 40°C for 8 h to obtain low molecular weight chitosan.
[0067] (4) Take 0.6 g of Tris-HCl buffer (pH = 8.0) and add it to 100 g of deionized water, disperse 1 g of low molecular weight chitosan in it, and ultrasonicate for 1 h; then add 1.6 g of BN@PDA, stir at room temperature for 24 h, wash with deionized water and ethanol three times, and vacuum dry at 60 ° C for 12 h to obtain BN@PDA-Chitosan.
[0068] (5) Mix BN@PDA-Chitosan with silane coupling agents KH550, KH560, and KH570 in a mass ratio of 5:4 and stir evenly.
[0069] (6) The obtained solution was reacted in a reactor at 85 °C for 3 h, and then dried and ground at 150 °C to obtain BN@PDA-Chitosan-KH550, BN@PDA-Chitosan-KH560, and BN@PDA-Chitosan-KH570, respectively.
[0070] 4g BN@PDA-Chitosan-HMDS (Example 1), 4g BN@PDA-Chitosan-KH550, 4g BN@PDA-Chitosan-KH560, and 4g BN@PDA-Chitosan-KH570 were added to 16g vinyl silicone oil and mixed evenly to obtain 20g of silicone-based adhesive; 10g of silicone-based adhesive and 0.01g of platinum catalyst (chloroplatinic acid) were mixed evenly to obtain component A; 10g of silicone-based adhesive and 1g of hydrogen-containing silicone oil were mixed evenly to obtain component B; components A and B were mixed evenly in a mass ratio of 1:1, placed in a vacuum drying oven at 30°C for degassing for 30 minutes, poured into a mold and cured at room temperature for 12 hours to obtain a thermally conductive insulating silicone potting adhesive, and its thermal conductivity was tested, and repeated 3 times.
[0071] Table 4
[0072]
[0073] As shown in Table 4, HMDS, KH550, KH560, and KH570 are all silane coupling agents, which are used for surface modification of thermal conductive insulating fillers. Silane coupling agents can form an active layer on the surface of solid powders. Its mechanism of action is to react the silicon-oxygen bond in the silane molecule with the hydroxyl group to form a hydrogen bond and condense into a -SiO-M covalent bond (M represents the group on the surface of the thermal conductive filler), thereby achieving surface modification and reducing the surface roughness of the composite material. KH550, KH560, and KH570 themselves will hydrolyze to produce a Si-O-Si partial cross-linked structure, which reduces the activity of the surface of the thermal conductive filler. KH550 is an aminosilane, KH560 is an epoxysilane, and KH570 is a methacryloxysilane. The amino group in KH550 is very active and easily reacts with the OH on the surface of the boron nitride modified with dopamine and chitosan, while the epoxy group and methacryloxy group are less active, so HMDS has the best surface modification effect on the thermal conductive filler.
[0074] Comparative Example 2 (the modification amount of the silane coupling agent is different from that of Example 1)
[0075] (1) Disperse 1 g of boron nitride in 150 g of deionized water, ultrasonicate for 3 h, and stir evenly.
[0076] (2) Add 0.6 g Tris-HCl buffer (pH = 8.0) and 0.6 g dopamine (DA) to the mixed solution obtained in step (1), stir in a water bath at 60° C. for 12 h at a speed of 500 r / min, and finally dry at 60° C. for 12 h to obtain BN@PDA.
[0077] (3) Add 5 g of 5 wt% H2O2 aqueous solution to 10 g of chitosan-acetic acid aqueous solution (containing 1 g of chitosan, 2 wt% of acetic acid, and an average molecular weight of chitosan of 100 KDa), stir in a water bath at 60°C for 8 h at a speed of 500 r / min, and filter through two layers of filter paper after cooling; adjust the pH of the filtrate to 10 with strong base NaOH, let stand for 2 h, and filter again with two layers of filter paper; concentrate the filtrate under reduced pressure, dilute with methanol, let stand for 5 h, collect the white precipitate by filtration, wash with methanol, and finally dry in a vacuum at 40°C for 8 h to obtain low molecular weight chitosan.
[0078] (4) Take 0.6 g of Tris-HCl buffer (pH = 8.0) and add it to 100 g of deionized water, disperse 1 g of low molecular weight chitosan in it, and ultrasonicate for 1 h; then add 1.6 g of BN@PDA, stir at room temperature for 24 h, wash with deionized water and ethanol three times, and vacuum dry at 60 ° C for 12 h to obtain BN@PDA-Chitosan.
[0079] (5) Mix BN@PDA-Chitosan and silane coupling agent hexamethyldisilazane (HMDS) in mass ratios of 5:2, 5:4, and 5:6, respectively, and stir evenly.
[0080] (6) The obtained solution was reacted in a reactor at 85 °C for 3 h, and then dried and ground at 150 °C to obtain BN@PDA-Chitosan-HMDS1, BN@PDA-Chitosan-HMDS2, and BN@PDA-Chitosan-HMDS3, respectively.
[0081] Add 4g BN@PDA-Chitosan-HMDS1 (mass ratio 5:2), 4g BN@PDA-Chitosan-HMDS2 (mass ratio 5:4), and 4g BN@PDA-Chitosan-HMDS3 (mass ratio 5:6) to 16g vinyl silicone oil, respectively, mix well, and obtain 20g silicone-based adhesive; mix 10g silicone-based adhesive and 0.01g platinum catalyst (chloroplatinic acid) to obtain component A; mix 10g silicone-based adhesive and 1g hydrogen-containing silicone oil to obtain component B; components A and B are mixed evenly in a mass ratio of 1:1, put into a vacuum drying oven at 30°C for degassing for 30 minutes, pour into a mold and cure at room temperature for 12 hours to obtain a thermally conductive insulating silicone potting adhesive, test its thermal conductivity, and repeat 3 times.
[0082] Table 5
[0083]
[0084] Silane coupling agent HMDS can form an active layer on the surface of solid powder. Its mechanism of action is to react the silicon-oxygen bond in the silane molecule with the hydroxyl group to form a silicon-oxygen-carbon bond, thereby achieving surface modification and reducing the surface roughness of the composite material. As shown in Table 5, the thermal conductivity of the silicone potting compound prepared by mixing BN@PDA-Chitosan with the silane coupling agent hexamethyldisilazane (HMDS) in a mass ratio of 5:4 is the largest. If the content of the silane coupling agent is too low, there will be less coupling agent grafted on the surface, while if the amount of coupling agent is too large, the condensation reaction of the coupling agent will reduce the coupling efficiency.
[0085] Comparative Example 3 (Chitosan is different from that in Example 1)
[0086] (1) Disperse 1 g of boron nitride in 150 g of deionized water, ultrasonicate for 3 h, and stir evenly.
[0087] (2) Add 0.6 g Tris-HCl buffer (pH = 8.0) and 0.6 g dopamine (DA) to the mixed solution obtained in step (1), stir in a water bath at 60° C. for 12 h at a speed of 500 r / min, and finally dry at 60° C. for 12 h to obtain BN@PDA.
[0088] (3) Take 0.6 g of Tris-HCl buffer (pH = 8.0) and add it to 100 g of deionized water, disperse 1 g of chitosan with an average molecular weight of 100 KDa in it, and ultrasonicate for 1 h; then add 1.6 g of BN@PDA, stir at room temperature for 24 h, wash with deionized water and ethanol for 3 times, and vacuum dry at 60 ° C for 12 h to obtain BN@PDA-Chitosan.
[0089] (4) Mix BN@PDA-Chitosan and silane coupling agent hexamethyldisilazane (HMDS) in a mass ratio of 5:4 and stir evenly.
[0090] (5) The obtained solution was reacted in a reactor at 85 °C for 3 h, and then dried and ground at 150 °C to obtain BN@PDA-Chitosan-HMDS.
[0091] 4g BN@PDA-Chitosan-HMDS (Example 1) and 4g BN@PDA-Chitosan-HMDS (Comparative Example 3) were added to 16g vinyl silicone oil, and mixed evenly to obtain 20g silicone-based adhesive. 10g silicone-based adhesive and 0.01g platinum catalyst (chloroplatinic acid) were mixed evenly to obtain component A, and 10g silicone-based adhesive and 1g hydrogen-containing silicone oil were mixed evenly to obtain component B. Components A and B were mixed evenly in a mass ratio of 1:1, placed in a 30°C vacuum drying oven for degassing for 30 minutes, poured into a mold and cured at room temperature for 12 hours to obtain a thermally conductive insulating silicone potting adhesive, and its thermal conductivity was tested, and repeated 3 times.
[0092] Table 6
[0093]
[0094] As shown in Table 6, the thermal conductivity of the low molecular weight chitosan prepared by acid hydrolysis and the thermal conductive filler composite test is higher than that of the untreated chitosan. Since the molecular weight of chitosan is reduced, the viscosity is reduced, the intermolecular force is weakened, and the dispersibility is improved, the thermal conductive filler modified by low molecular weight chitosan has improved compatibility and increased thermal conductivity. The volume resistances in Example 1 and Comparative Example 3 are not the same, which is due to the omission of n digits after the decimal point in the volume resistance data. In fact, the volume resistance of Comparative Example 3 is slightly smaller than that of Example 1.
[0095] The above embodiments of the present invention are merely examples for illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a thermally conductive insulating filler modified by polyphenol compounds, characterized in that: The steps include: Step 1: Disperse the thermally conductive insulating filler in water, add an alkaline solvent and a polyphenol compound, and stir until the mixture is uniformly mixed; the resulting solution is washed, centrifuged, dried, and ground to obtain a solid powder; Step 2: dropping a hydrogen peroxide aqueous solution into a chitosan-acetic acid aqueous solution, and after reaction, obtaining low molecular weight chitosan; Step 3: adding low molecular weight chitosan to an alkaline solvent for ultrasonic dispersion, then adding solid powder for stirring, washing and drying to obtain a modified solid powder; Step 4: Mix the modified solid powder with hexamethyldisilazane and stir evenly. After the obtained solution reacts in a reactor, it is dried and ground to obtain a modified thermally conductive insulating filler.
2. The method for preparing a thermally conductive insulating filler modified by polyphenol compounds according to claim 1, characterized in that: Step 1: The ratio of the added amounts of the thermally conductive insulating filler, water, alkaline solvent and polyphenol compound is 0.8-2g:150-300mL:0.6-1g:0.4-1g.
3. The method for preparing a thermally conductive insulating filler modified by polyphenol compounds according to claim 1, characterized in that: Step 1: The thermally conductive insulating filler is a mixture of one or more of boron nitride, aluminum nitride, and silicon nitride; the thermally conductive insulating filler is dispersed in water, ultrasonicated for 3-4 hours and stirred for 2-3 hours, and then an alkaline solvent and a polyphenol compound are added.
4. The method for preparing a thermally conductive insulating filler modified by polyphenol compounds according to any one of claims 1 to 3, characterized in that: Step 1, the alkaline solvent is one of Tris-HCl buffer, sodium carbonate, sodium bicarbonate, and borate buffer; the polyphenol compound is one of dopamine, catechol, tannic acid, catechol, and gallic acid.
5. The method for preparing a thermally conductive insulating filler modified by polyphenol compounds according to any one of claims 1 to 3, characterized in that: Step 1, the stirring is: stirring in a water bath at 60-70°C, rotating speed 400-600r / min, and continuous stirring time 12-24h.
6. The method for preparing a thermally conductive insulating filler modified by polyphenol compounds according to claim 1, characterized in that: Step 2 specifically includes the following steps: dripping a hydrogen peroxide aqueous solution into a chitosan-acetic acid aqueous solution, magnetically stirring the mixture at 60-70° C. for 8-10 hours, then cooling and filtering, adjusting the pH of the filtrate to 10-10.5, standing and filtering again; concentrating the filtrate under reduced pressure, diluting it with methanol, standing and filtering to collect a white precipitate, washing it with methanol, and vacuum drying to obtain low molecular weight chitosan.
7. The method for preparing a thermally conductive insulating filler modified by polyphenol compounds according to claim 1 or 6, characterized in that: Step 3: The mass ratio of the low molecular weight chitosan, the alkaline solvent and the solid powder is 1:100:1.5-1.7; and the stirring is carried out at room temperature for 24-30 hours.
8. The method for preparing a thermally conductive insulating filler modified by polyphenol compounds according to claim 1, characterized in that: Step 4: The mass ratio of the modified solid powder to hexamethyldisilazane is 5:
4.
9. The method for preparing a thermally conductive insulating filler modified by polyphenol compounds according to claim 1 or 8, characterized in that: Step 4, the reaction conditions of the reactor are: temperature of 85-90°C, duration of 2-3h; the drying conditions are: temperature of 150-160°C, duration of 6-12h.
10. Use of the modified thermally conductive insulating filler prepared by the preparation method according to any one of claims 1 to 9 in silicone potting adhesive.
